A Transitivity Analysis of Ria Ricis And Atta Halilintar’s Promotional Captions on Instagram - Putri Rizki Lestari (Passage, 2019)
This study aims to discover the lexico-grammatical features and social function of Ria Ricis and Atta Halilintar’s, promotional captions on Instagram. There were some frameworks used to guide this research, such as Gerot and Wignell’s explanations about the lexico-grammatical features and social function of descriptive, procedure, and recount text (1995), and Halliday’s transitivity analysis (2014). The qualitative method was used to conduct this research. The results show that promotional captions could consist of descriptive, procedure, and recount texts with different lexico-grammatical features and social function for each text type. Relational Processes dominate descriptive texts, while Material Processes appear frequently in procedure texts. In terms of recount texts, Ria Ricis’ recount texts are dominated by Material Processes while Atta Halilintar’s recount texts contain Material Processes, Mental Processes, and Behavioral Processes. The social function of promotional caption is to sell products and services online. However, each text type has different social function. In promotional captions, procedure texts are used to give the readers instruction on how to buy or get more information about the products. Meanwhile, recount texts are used to tell the readers about the Ria Ricis and Atta Halilintar’s past experiences which are related to the products. Lastly, descriptive texts are used to give details about the products. Keywords: caption, Instagram, lexicogrammar, promotion, social function